Sleep changes during social isolation due to the Covid-19 pandemic in individuals with chronic respiratory diseases - Dala Pola, Daniele (2024)
Objective: To analyze and compare the impact of social isolation due to the COVID-19 pandemic on sleep assessed at two time points (visit 1: during strict social isolation; visit 2: after the relaxation of social isolation measures) in individuals with stable chronic obstructive pulmonary disease (COPD), asthma, and interstitial lung disease (ILD), all of whom were not infected with COVID-19. Method: In a one-year prospective cohort study, individuals were evaluated concerning lung function (via spirometry), demographic and clinical data, and sleep objectively assessed through actigraphy over 7 consecutive days at both visits. Result: A total of 36 individuals (12 with COPD, 10 with asthma and 14 with ILD) were included. There was significant decline in sleep quality at visit 2 compared to visit 1 across all three diseases, primarily in the parameters of sleep efficiency, fragmentation and wake time after sleep onset; however, the total sleep duration did not change. Furthermore, individuals with ILD exhibited a smaller variation in both the number and duration of vigilance blocks compared to those with the other two diseases, indicating lower sleep fragmentation. Conclusion: Regardless of the disease (COPD, asthma, or ILD), individuals with chronic respiratory conditions who were not infected with COVID-19 experienced decline of sleep quality following the period of social isolation. Additionally, individuals with ILD appear to have been less impacted (with lower sleep fragmentation) compared to those with the other diseases.